Měřič odběru USB zařízení - Macek, Josef (Vysoké učení technické v Brně. Fakulta elektrotechniky a komunikačních technologií, 2024)
Tato bakalářská práce je zaměřena na konstrukci USB zařízení, které umožňuje monitorovat elektrické parametry, jako jsou napětí a proud, a následně vypočítat spotřebu energie. Práce obsahuje teoretickou část, ve které se čtenář seznámí s historií USB technologie, jejími typy a specifikacemi. Také se zde pojednává o technologiích rychlonabíjení USB. V závěrečné podkapitole teoretické části jsou uvedeny součástky vhodné pro výrobu tohoto zařízení. Praktická část se věnuje návrhu schématu zařízení a desky plošných spojů, programování mikročipu a samotnému testování. Závěr práce shrnuje poznatky získané při výrobě zařízení a nabízí možnosti dalšího rozšíření.

This bachelor's thesis focuses on the construction of a USB device that allows monitoring of electrical parameters, such as voltage and current and subsequently calculates energy consumption. The thesis contains a theoretical section where the reader is introduced to the history of USB technology, its types and specifications. It also discusses USB fast charging technologies. In the final section of the theoretical section the components suitable for creating this device are listed. The practical section deals with the design of the device's schematic and printed circuit board, programming the microchip and the actual testing. The conclusion summarizes the findings from the device's production and suggests further options for expanding the device's capabilities.
Power meter for USB devices
Keywords: USB technologie. USB Power Delivery. Rychlonabíjení USB. Návrh schématu zařízení. Návrh PCB.; USB technology. USB Power Delivery. USB fast charging. Design of device schematics. PCB design.